2007
DOI: 10.1038/sj.cdd.4402232
|View full text |Cite
|
Sign up to set email alerts
|

An essential role for the Leishmania major metacaspase in cell cycle progression

Abstract: Metacaspases (MCAs) are distant orthologues of caspases and have been proposed to play a role in programmed cell death in yeast and plants, but little is known about their function in parasitic protozoa. The MCA gene of Leishmania major (LmjMCA) is expressed in actively replicating amastigotes and procyclic promastigotes, but at a lower level in metacyclic promastigotes. LmjMCA has a punctate distribution throughout the cell in interphase cells, but becomes concentrated in the kinetoplast (mitochondrial DNA) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
95
1
18

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(116 citation statements)
references
References 41 publications
2
95
1
18
Order By: Relevance
“…12 Nevertheless, RNA interference of the three MCAs together resulted in a rapid arrest of growth with a delay in kinetoplast segregation and a cytokinesis block. In addition, Ambit et al 13 showed that limited levels of LmjMCA are essential for normal cell proliferation. As T. cruzi lacks components necessary for the RNA interference pathway, 33 and knockout strategies are restricted to non-essential single copy genes, we decided to study metacaspase overexpression in the different life-cycle stages with an inducible vector.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Nevertheless, RNA interference of the three MCAs together resulted in a rapid arrest of growth with a delay in kinetoplast segregation and a cytokinesis block. In addition, Ambit et al 13 showed that limited levels of LmjMCA are essential for normal cell proliferation. As T. cruzi lacks components necessary for the RNA interference pathway, 33 and knockout strategies are restricted to non-essential single copy genes, we decided to study metacaspase overexpression in the different life-cycle stages with an inducible vector.…”
Section: Discussionmentioning
confidence: 99%
“…5 Their substrate specificity is for basic residues at P1 position, making them unable to cleave caspase substrates. 6 Evidences suggest that metacaspases modulate cell death, [7][8][9][10][11] cell cycle progression [12][13][14] and protein aggregation, 15 but there is still controversy about their functions and their relation with caspases. [16][17][18] The fact that metacaspases are not present in humans and fulfil important roles in trypanosomatids make them attractive drug targets, and a first series of inhibitors with trypanocidal activity has been developed recently.…”
mentioning
confidence: 99%
“…Furthermore, the L. major metacaspase seems to have an essential function in cell-cycle progression rather than in PCD. 28 And, in T. brucei, metacaspases appear to be associated with RAB11-positive endosomes, 15 and not to intervene in apoptosis. Still, intriguingly, some reports have described 'caspase-like' activities in these protozoa.…”
Section: Discussionmentioning
confidence: 99%
“…Also they implicated L. major active metacaspase has effective role in the separation of the nucleus and the kinetoplast, function that could be independent of PCD. 26 In this study, PARP and metacaspase gene expression increased simultaneously. This evolution could repair cell DNA damage.…”
Section: Miltefosine Induces Sub-g0/g1 Phase Cell-division Arrestmentioning
confidence: 80%
“…In mammalians, caspases do not only function in PCD, but they also have functions in cell proliferation and differentiation. 11 Ambit et al 26 found that LmjMCA is expressed in actively replicating amastigotes and procyclic promastigotes, but at a lower level in metacyclic promastigotes. Over expression of LmjMCA in promastigotes leads to severe growth retardation.…”
Section: Miltefosine Induces Sub-g0/g1 Phase Cell-division Arrestmentioning
confidence: 99%